ANALYZING TEACHERS’ EVALUATION ON THEIR PEDAGOGICAL COMPETENCE - Sudiantoro Sudiantoro; Regina Regina; Ikhsanudin Ikhsanudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to analyze the teachers’ evaluation on their pedagogical competence and strategies to enhance their pedagogical competence. In this study, the case was the English Teachers’ Pedagogical competence weaknesses in Teluk Batang. This case study involved six English teachers of SMPN at Teluk Batang district. The data collecting technigues used in this  study were observation, field notes, interview and questionnaire. The researcher analyzed the teachers’ evaluation on their pedagogical competence using the standard application recommended by the National Education Department. The results of the analysis showed that the teachers needed improvement in assessment and evaluation competence. Therefore, the researcher proposed strategies that available for the teachers to enhance their pedagogical competence, those are; effective classroom management; effective teaching practice; effective assessment; and technology skill.Keywords : Case Study,  Pedagogical Competence,  Teachers’ Evaluation